Validation of UV spectrophotometric method for determination of lomefloxacin in pharmaceutical dosage form - Gomes, Greici Cristiani [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2005)
A simple and reproducible method was developed for the assay of lomefloxacin in tablets. The excipients in the commercial tablet preparation did not interfere with the assay. Beer's law is obeyed in the range 2.0-9.0 μg.mL-1 at λmax 280 nm. The molar absorptivity was calculated. Six triplicate analyses of solutions containing six different concentrations of the examined drug were carried out and gave a mean correlation coefficient 0.9997. The proposed method was applied to the determination of the examined drug in coated tablet and the results demonstrated that the method is equally accurate, precise and reproducible as the official methods.
Keywords: Fluoroquinolone; Lomefloxacin; Quality Control; Spectrophotometry; lomefloxacin; accuracy; analytic method; correlation coefficient; drug absorption; drug coating; drug determination; drug manufacture; drug synthesis; tablet; ultraviolet spectrophotometry; validation process